Efficacy of a vectorized anti‐tau antibody using systemic dosing of a blood brain barrier penetrant AAV capsid in mouse models of tauopathies. (31st December 2021) - Liu, Wencheng; Holth, Jerrah; Paranjpe, Maneesha; Ren, Xiao‐Qin; Shu, Yanqun; Murlidharan, Giridhar; Chung, Charlotte; Powers, Alex; Peterson, Emalee; Ecker, Abigail; Hameedi, Usman; Grant, Kyle; et al.
Abstract: Background: Anti‐tau immunotherapy is a promising therapy for tauopathies, including Alzheimer's disease (AD), frontotemporal dementia (FTD) and progressive supranuclear palsy (PSP). While passive immunization with anti‐tau monoclonal antibodies has been shown by several laboratories to reduce age‐dependent tau pathology and neurodegeneration in mouse tauopathy models, these studies have typically used repeated high weekly doses of antibody and reported only moderate reduction of tau pathology. To circumvent these limitations, using an adeno‐associated virus (AAV) vector to deliver a tau monoclonal antibody into hippocampus by direct injection to the location have been described. High levels of antibody and marked reduction of tau pathology is achieved by this approach. To further optimize this approach with a lesser invasive administration route, we have previously demonstrated broad distribution and expression of a vectorized anti‐tau antibody in the mouse brain using a blood‐brain barrier (BBB) penetrant AAV capsid administered intravenously (IV). This gene therapy‐based approach has potential advantages, including continuous expression of antibody in the central nervous system (CNS) after a single administration of vector, increased CNS levels of tau antibody relative to passive immunotherapy, and the potential to target intracellular tau aggregates. Here we describe studies characterizing the onset of transduction following dosing with a vectorized tau antibody and its efficacy in mouse models of tauopathy. Method: AAV vectors comprising the BBB‐penetrant AAV capsid and a transgene encoding an anti‐tau monoclonal antibody were administered by IV bolus to mouse models of tauopathy. Biodistribution and cellular tropism in the CNS were evaluated by ELISA and (or) immunostaining. Tau pathology was measured by AT100 immunohistochemistry and AT8 ELISA. Result: We then investigated efficacy in reduction of tau pathology in mouse tauopathy models. Treatment with our vectorized antibody resulted in durable antibody expression in the CNS and a corresponding reduction in CNS insoluble pathological tau and neurofibrillary tangles. Conclusion: Our results indicate that systemic dosing of a vectorized anti‐tau antibody using a BBB‐penetrant AAV capsid results in reduced tau pathology and may represent a new single‐dose therapeutic strategy for treating various tauopathies.